Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/gmd-2021-231
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introducing CRYOWRF v1.0: Multiscale atmospheric flow simulations with advanced snow cover modelling

Abstract: Abstract. Accurately simulating snow-cover dynamics and the snow-atmosphere coupling is of major importance for topics as wide-ranging as water resources, natural hazards and climate change impacts with consequences for sea-level rise. We present a new modelling framework for atmospheric flow simulations for cryospheric regions called CRYOWRF. CRYOWRF couples the state-of-the-art and widely used atmospheric model WRF, with the detailed snow-cover model SNOWPACK. CRYOWRF makes it feasible to simulate dynamics o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…Although Orsolini et al (2019) do not find a mass effect of including blowing snow sublimation in ERA5, Chung et al (2011) for instance computed a larger effect of blowing snow sublimation of 12 mm yr −1 over sea ice over 324 d. The non-existent blowing snow particle sublimation may be a reason for the overestimation tendency found in our study. Recent results with a new model of drifting snow sublimation (CRYOWRF; Sharma et al, 2021) indicate that it may be more important than previously estimated. We plan to address this particular problem in our future work.…”
Section: Era5 Performancementioning
confidence: 99%
“…Although Orsolini et al (2019) do not find a mass effect of including blowing snow sublimation in ERA5, Chung et al (2011) for instance computed a larger effect of blowing snow sublimation of 12 mm yr −1 over sea ice over 324 d. The non-existent blowing snow particle sublimation may be a reason for the overestimation tendency found in our study. Recent results with a new model of drifting snow sublimation (CRYOWRF; Sharma et al, 2021) indicate that it may be more important than previously estimated. We plan to address this particular problem in our future work.…”
Section: Era5 Performancementioning
confidence: 99%
“…For such an approach, the present work has shown that the semi‐empirical snow model Δsnow provides a computationally efficient basis for high elevation regions in the cold season without melt. For more elaborate investigations on the impact of dry and wet snow metamorphism on the snow isotope profile, a fully coupled atmosphere‐snow modeling system would be needed such as CRYOWRF (Sharma et al., 2021), which requires the implementation of isotope physics in a thermodynamic snow model such as SNOWPACK.…”
Section: Discussionmentioning
confidence: 99%
“…Simulations are performed with the non-hydrostatic, fully compressible Weather Research and Forecasting (WRF) model version 4.2 (Skamarock et al, 2008) and the recently implemented CRYOWRF v1.0 (Sharma et al, 2021), which couples WRF version 4.2 to the snow model SNOWPACK (Lehning et al, 1999) as a land surface model. In CRYOWRF, drifting snow processes are represented near the surface on a high resolution vertical grid between the surface and the first model level of WRF (Sharma et al, 2021).…”
Section: Wrf and Cryowrfmentioning
confidence: 99%
“…The recently developed version of WRF, called CRYOWRF (Sharma et al, 2021) allows for a more physical representation of snow transport and blowing snow sublimation. In CRYOWRF, blowing snow is treated online in a non-hydrostatic atmospheric model, allowing to investigate the full chain of interactions between blowing snow and the atmosphere at scales ranging from mesoscale to the turbulent scales.…”
Section: Introductionmentioning
confidence: 99%